Leymus chinensis resists degraded soil stress by modulating root exudate components to attract beneficial microorganisms - Lin, Yulong; Mei, Linlin; Wei, Qianhao; Li, Bing; Zhang, Pan; Sun, Shixuan; Cui, Guowen (Frontiers in Microbiology, 2022)
Phytoremediation is an effective means to improve degraded soil nutrients and soil structure. Here, we investigated the remediation effects of Leymus chinensis (L. chinensis) on the physicochemical properties and structure of degraded soil after 3 years of cultivation and explored the bacterial and fungal drivers in root exudates by metabolomics and high-throughput sequencing. The results showed that root exudates increased soil organic matter (SOM), total nitrogen (TN), total phosphorus (TP) and soil aggregates, and organic acids in root exudates reduced pH and activated insoluble nutrients into forms that are available to plants, such as available nitrogen (NH4+-N), nitrate nitrogen (NO3−-N), and available phosphorus (AP). The cultivation of L. chinensis restored the diversity and richness of soil microorganisms and recruited potential beneficial bacteria and fungi to resist degraded soil stress, and L. chinensis also regulated the abundances of organic acids, amino acids and fatty acids in root exudates to remediate degraded soils. Spearman correlation analysis indicated that glutaric acid, 3-hydroxybutyric acid and 4-methylcatechol in root exudates attracted Haliangium, Nitrospira and Mortierella to the rhizosphere and dispersed the relative abundance of the harmful microorganisms Fusicolla and Fusarium. Our results demonstrate that L. chinensis enhances soil fertility, improves soil structure, promotes microbial diversity and abundance, and recruits potentially beneficial microorganisms by modulating root exudate components.